Anemia as an Under-Recognized Cause of Angina Pectoris (University Heart Journal, 2026)
Background: Angina pectoris is traditionally attributed to obstructive coronary artery disease (1,2); however, myocardial ischemia may arise from systemic factors that impair oxygen delivery. Anemia, highly prevalent in South Asia and other low- and middle-income regions (6), reduces arterial oxygen content and can precipitate angina even in the absence of significant epicardial coronary stenosis (10,11). Despite its frequency, anemia remains insufficiently emphasized in routine cardiology evaluation.Objective: To examine the mechanisms by which anemia induces myocardial ischemia and angina, and to outline its diagnostic, therapeutic, and prognostic implications in contemporary cardiovascular practice.Methods: A focused review of cardiovascular and hematologic literature was performed, emphasizing oxygen transport physiology, coronary hemodynamics, and clinical studies linking anemia with ischemic symptoms (4,6).Results: Reduced hemoglobin concentration lowers arterial oxygen content, prompting compensatory increases in heart rate and cardiac output that raise myocardial oxygen demand (1,7). When coronary vasodilatory reserve is limited due to epicardial disease or microvascular dysfunction (10,11), these adaptations fail, resulting in oxygen supply–demand mismatch and angina. Correction of anemia improves functional capacity and anginal burden in selected populations (4,8).Conclusion: Anemia is a clinically important and potentially reversible contributor to angina pectoris.University Heart Journal 2026; 22(1): 41-43